2007
DOI: 10.1073/pnas.0701617104
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin B1 and B2 receptors both have protective roles in renal ischemia/reperfusion injury

Abstract: To explore the role of the kallikrein-kinin system in relation to ischemia/reperfusion injury in the kidney, we generated mice lacking both the bradykinin B1 and B2 receptor genes (B1RB2R-null, Bdkrb1 ؊/ ؊/Bdkrb2 ؊/؊ ) by deleting the genomic region encoding the two receptors. In 4-month-old mice, blood pressures were not significantly different among B1RB2R-null, B2R-null (Bdkrb2 ؊/؊ ), and WT mice. After 30 min of bilateral renal artery occlusion and 24 h of reperfusion, mortality rates, renal histological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
87
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 60 publications
8
87
0
6
Order By: Relevance
“…The kinins, acting through B2R also increase the expression of inducible NOS (iNOS) (39). Our previous finding that preprandial levels of plasma nitrite/nitrate are lower in BRKO mice than in WT (23), and another report showing that urinary nitrite/nitrate excretion in B2R-null mice is lower than in WT (40) suggest that the KKS is also important in basal NO production.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The kinins, acting through B2R also increase the expression of inducible NOS (iNOS) (39). Our previous finding that preprandial levels of plasma nitrite/nitrate are lower in BRKO mice than in WT (23), and another report showing that urinary nitrite/nitrate excretion in B2R-null mice is lower than in WT (40) suggest that the KKS is also important in basal NO production.…”
Section: Discussionmentioning
confidence: 91%
“…Mice lacking B2R gene or having the diabetogenic Akita mutation (C96Y) in the insulin 2 gene of the C57BL/6 strain were purchased from Jackson Laboratory. Mice lacking both B1R and B2R of a pure C57BL/6 background were generated as previously described (23). All experiments were approved by the University of North Carolina Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies [28][29][30][31] show that deletion of B1R and B2R exacerbates the renal phenotype in diabetic mouse models, suggesting that both receptors have a protective effect on diabetic nephropathy by suppressing oxidative stress via NO and prostaglandins. However, because the absence of one of the receptors causes increased expression of the other, it is difficult to determine the precise function of each receptor [28] .…”
mentioning
confidence: 99%
“…Kinin receptors in renal tissue were studied in the I/R model, where it was shown that both receptors have a protective role in this type of injury [30] . However, a different study [15] found that during I/R in mice, the double knockout showed an extremely high SCr along with a proinflammatory profile.…”
mentioning
confidence: 99%